Radiolytic degradation of thiophene: Performance, pathway and toxicity evaluation. (December 2021) - He, Hang; Wang, Shizong; Wang, Jianlong
Abstract: Thiophene is one of typical refractory organic pollutants in coal chemical wastewater, which cannot be effectively removed by traditional biological treatment processes. In this study, ionizing radiation was used to degrade thiophene. The effect of absorbed dose, initial concentration and pH on the thiophene degradation was investigated. The results showed that thiophene could be completely degraded when the its initial concentration was 5 mg/L, the pH was 9, and the absorbed dose was 5 kGy. The results of quenching experiments indicated that all the hydroxyl radicals, hydrated electron and hydrogen radicals were responsible for the degradation of thiophene, which explained the wide range of pH application for the thiophene degradation by ionizing radiation. Four degradation intermediates were identified, including thiophene 1-oxide, thiophen-2-ol, 2, 3-dihydrothiophen-2-ol and acetic acid, and two possible pathways of thiophene degradation were thus proposed. Ecological structure activity relationships program analysis suggested that thiophene 1-oxide and thiophen-2-ol were more toxic than thiophene. In general, ionizing radiation is an effective technology for thiophene degradation. Highlights: Thiophene could be effectively degraded by Gamma radiation. The effect of dose, concentration and pH on thiophene degradation was examined. Possible degradation schemes of thiophene were proposed. Ionizing radiation is an effective technology for thiophene degradation.